2021
DOI: 10.1002/advs.202100626
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic Screening During Somatic Cell Reprogramming Identifies DKK3 as a Roadblock of Organ Regeneration

Abstract: Somatic cell reprogramming and tissue repair share relevant factors and molecular programs. Here, Dickkopf-3 (DKK3) is identified as novel factor for organ regeneration using combined transcription-factor-induced reprogramming and RNA-interference techniques. Loss of Dkk3 enhances the generation of induced pluripotent stem cells but does not affect de novo derivation of embryonic stem cells, three-germ-layer differentiation or colony formation capacity of liver and pancreatic organoids. However, DKK3 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 98 publications
(152 reference statements)
0
14
0
Order By: Relevance
“…In this context, Dkk3 knockout increased recovery rates by limiting canonical Wnt signaling and increasing Hedgehog (Hh) signaling during pancreatic regeneration. These effects have been proposed to involve a reduction in the expression of the transcriptional repressor Gli3 [ 73 ]. The same study reported a similar scenario in the context of liver regeneration, leading the authors to propose that Dkk3 functions as a roadblock in liver and pancreas repair/regeneration upon injury [ 73 ].…”
Section: Dkk-3 As a Regulator Of Tumor Stromal Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, Dkk3 knockout increased recovery rates by limiting canonical Wnt signaling and increasing Hedgehog (Hh) signaling during pancreatic regeneration. These effects have been proposed to involve a reduction in the expression of the transcriptional repressor Gli3 [ 73 ]. The same study reported a similar scenario in the context of liver regeneration, leading the authors to propose that Dkk3 functions as a roadblock in liver and pancreas repair/regeneration upon injury [ 73 ].…”
Section: Dkk-3 As a Regulator Of Tumor Stromal Cellsmentioning
confidence: 99%
“…These effects have been proposed to involve a reduction in the expression of the transcriptional repressor Gli3 [ 73 ]. The same study reported a similar scenario in the context of liver regeneration, leading the authors to propose that Dkk3 functions as a roadblock in liver and pancreas repair/regeneration upon injury [ 73 ]. Dkk-3 activation of non-canonical Wnt/β-catenin-independent signaling involving c-JUN N-terminal kinase (JNK) increases the secretion of inflammatory factors, such as TNF-α and IL-1β, in the brain, suggesting a neuroprotective mechanism [ 74 ] Furthermore, Dkk-3 is a factor required for smooth muscle cell differentiation [ 74 ]; the absence of Dkk-3 may therefore contribute to accelerating blood vessel inflammation and subsequent atherosclerotic plaque formation.…”
Section: Dkk-3 As a Regulator Of Tumor Stromal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional genomic screening using gain-and loss-offunction technologies was successfully used to identify gene networks governing human embryonic stem cell behavior [24]. Our own group recently reported Dickkopf-3 (DKK3) as a novel factor for organ regeneration using combined transcription-factor-induced reprogramming and RNA interference techniques [25]. However, RNA interference screening during pancreatic endoderm formation has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are essential regulators of embryomorphic pathways that are reactivable in response to tissue damage and are involved in epithelial-mesenchymal transition and fibrosis through various molecular mechanisms [ 1 , 2 , 3 ]. In particular, DKK3 is expressed in different organs, such as the heart, liver, eyes, uterus, embryo, placenta, blood, and pancreatic β cells [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. DKK3 has been described as a pleiotropic protein implicated in several cellular pathways involved in the cell cycle and differentiation.…”
Section: Introductionmentioning
confidence: 99%